Hunters of Dune - Herbert, Brian; Anderson, Kevin J., 1962- (Herbert, Frank. Dune series., 2007)
A group of refugees escapes on a ship into the uncharted reaches of the galaxy, seeking safety with the assistance of Paul Muad'Dib and Lady Jessica, revived with the help of genetic technology, while avoiding the diabolical traps of the Enemy.